PENGARUH DEBT TO EQUITY RATIO, EARNING PER SHARE DAN NET PROFIT MARGIN TERHADAP RETURN SAHAM PADA INDUSTRI FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011- 2016 - Adria Wuri Lastari (Fakultas Hukum dan Ekonomi Bisnis, 2018)
The purpose of this study was to analyze the effect of Debt to Equity Ratio, Earning Per Share and Net Profit Margin Against Return of Food and Beverages Industry Stock Listed on Indonesia Stock Exchange Period 2011-2016. Stock return is the result of investment activity. The problem of this research is whether there is any influence of Debt to Equity Ratio (DER), Earning Per Share (EPS) and Net Profit Margin (NPM) partially or simultaneously to stock return.The population of this research is Food and Beverages company listed in Indonesia Stock Exchange. The sample in this research is Food and Beverages Industry Company which consistently listed on BEI 2011 until 2016 that is 9 companies. The data collected were analyzed by using multiple linear regression analysis with partial test hypothesis test (t test) and simultaneous test (Test F). Hypothesis test using t statistic to test the partial variable influence and F-statistic test to test the variables jointly to stock return with level of significance 5%. In addition, a classical assumption test that includes normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. The result of regression analysis of data shows the following equation Y = 5,663 - 0,173 X1 + 0,23 X2 + 0,32 X3. Based on multiple regression analysis, it shows partially that DER, EPS and NPM have negative but not significant influence. And simultaneously (simultaneously) all the variables also have no significant effect. The magnitude of the effect of DER, EPS and NPM on Return on Food and Beverages sector in Indonesia Stock Exchange period 2011-2016 is 3.10% while the rest of 96.0% is determined by other factors not specified in this research. The conclusion of this research is that there is no partial and simultaneous influence of fundamental factor that is ratio of DER, EPS and NPM to stock return. For investors it is advisable to consider the external factors of the company in addition to fundamental factors such as economic conditions both nationally and globally, political and legal conditions for investment decisions in a company more appropriate